Relationship Between Age, Education, And Income With Contribution Compliance Of The National Health Insurance Program (JKN) In Bekasi Regency - Anom Dwi Prakoso; Ice Marini; Lyliana Endang Setianingsih; Afif Wahyudi Hidayat; Emmelia Kristina Hutagaol; Triseu Setianingsih (Sean Institute, 2023)
The National Health Insurance (JKN) is a government program that aims to ensure that all people can be healthy, productive, and prosperous. Compliance with paying contributions on time every month is the obligation of every JKN participant. The more participants who are in arrears of contributions can result in a large burden of health costs borne by BPJS for operations and the return of benefits to beneficiary participants. This can result in a deficit in the BPJS budget and the cross-subsidy scheme or the cooperation principle of the JKN program not working. The purpose of this study was to analyze the relationship between age, education and income with adherence to paying JKN contributions for independent participants in Bekasi Regency. This type of quantitative research uses an analytic observational design with a cross-sectional approach. The variables in the study include the independent variables (age, education, income) and the dependent variable (compliance with paying JKN contributions). The population includes all people who live in Bekasi Regency. The total sample studied was 210 subjects. Determination of the sample using the rule of thumb method with purposive sampling technique. The results of data analysis using the Spearman rank test showed that compliance with paying JKN contributions had a significant relationship with age (r=0.212; p=0.002), education (r=0.214; p=0.003), and income (r=0.156; p=0.023). Age, education, and income have been shown to have a statistically significant positive correlation with compliance with paying JKN contributions for independent participants in Bekasi Regency. The population includes all people who live in Bekasi Regency.